Tinjauan Teori Al-Mashlahah Al-Buthi Terhadap Hak Anak dalam Perspektif Hukum Islam dan Perjanjian Internasional - Achmad Shobirin Hasbulloh; Ahmadi Hasan; Masyithah Umar (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
Abstract This paper discusses children's rights in the perspective of Islamic law and international treaties and compares them using al-Buthi's al-mashlahah theory contained in his book entitled "Dlawābith al-Mashlahah fî al-Syarî'ah al-Islāmiyyah" with the aim of knowing which perspective is more accommodating to the benefit of children. This type of research is library research with a qualitative approach. According to al-Buthi, al-mashlahah becomes a proof if it is in line with maqashid al-syariah, does not contradict the Qur'an, does not contradict the Prophetic Hadith, does not contradict qiyas, and does not eliminate stronger benefits or commensurate benefits. Children's rights in the perspective of Islamic law include rights before birth and rights after birth. International treaties (Convention on the Rights of the Child) pay more attention to children's rights when they are born, so that many children's rights are forgotten. The provisions of Islamic Law regarding children's rights before and after birth are more in line with al-Buthi's al-mashlahah theory than the Convention on the Rights of the Child because they are in line with maqāshid al-syarî'ah. Children's rights should not only be in line with the child's benefit in the world, but must also be in line with the benefit for him in the hereafter. Islam has established the rights of children that benefit them in this world and in the hereafter. Keywords: Al-Buthi, Al-Mashlahah, Children's Rights, Islam, Convention Abstrak: Tulisan ini membahas hak anak dalam perspektif hukum Islam dan perjanjian internasional dan membandingkan antara keduanya menggunakan teori al-mashlahah al-Buthi yang termuat dalam kitab yang berjudul “Dlawābith al-Mashlahah fî al-Syarî’ah al-Islāmiyyah” dengan tujuan untuk mengetahui perspektif mana yang lebih mengakomodir kemaslahatan bagi anak. Jenis penelitian ini adalah penelitian kepustakaan dengan pendekatan kualitatif. Menurut al-Buthi, al-mashlahah menjadi hujjah jika selaras dengan maqashid al-syariah, tidak bertentangan dengan al-Quran, tidak bertentangan dengan hadis nabawi, tidak bertentangan dengan qiyas, dan tidak menghilangkan kemaslahatan yang lebih kuat atau kemaslahatan yang sepadan. Hak anak dalam perspektif hukum Islam meliputi hak sebelum dilahirkan dan hak sesudah dilahiran. Perjanjian internasional (Konvensi Hak Anak) lebih memperhatikan hak anak saat telah dilahirkan saja sehingga banyak sekali hak anak yang terlupakan. Ketetapan Hukum Islam mengenai hak anak sebelum dan sesudah dilahirkan lebih sesuai dengan teori al-mashlahah al-Buthi daripada Konvensi Hak Anak karena sejalan dengan maqāshid al-syarî’ah. Hak anak seyogyanya tidak hanya sejalan dengan kemaslahatan anak di dunia, melainkan juga harus selaras dengan kemaslahatan untuknya di akhirat. Islam telah menetapkan hak anak yang bermanfaat baginya di dunia dan di akhirat. Kata Kunci: Al-Buthi, Al-Mashlahah, Hak Anak, Islam, Konvensi